Prospects for Leaving the Population Out of Poverty - Javmanov, Jamshed; Radjabov, Navruzbek; Uralov, Baxtiyor; Fayzullayev, Umidullo (GREEN ECONOMY AND DEVELOPMENT, 2024)
This article examines and analyzes the prospects for lifting the population out of poverty, real total income per capita, average nominal monthly wage, average income of each family, poverty level indicators in the Samarkand region in 2023, family businesses in the Narpay district.